Speech Act Verbs in AlKashaf An Hakaek Al Sonan for Al-Tibi(743AH) - Hmad, Ali Abdullah; Khatab, Rebwar Abdullah (Journal of Tikrit University for Humanities, 2024)
Pragmatics pertains to the study of language within the context of its use. Verbal acts constitute a significant part of its constituent elements, facilitating the attainment of objectives via linguistic actions, so elucidating pragmatic significances and communicative objectives. This research is based on a doctoral dissertation titled "Trading Dimensions in Al-Kashif and Hakaik Al-sunan for the Tibi (743AH)." It aims to shed light on verbal verbs using Searle's division while examining the origins of this theory among an ancient Arab scholar in the sixth century AH. The study also aims to identify the purposes of this theory and propose ways to modify and strengthen the performing force, as well as how to shift from literal to implicit meaning. The author employs various methods to study the prophetic discourse and aims to bring the concepts used for analysis closer to a practical perspective.